The unlawful absence of a religious in a religious house as a cause of ipso facto dismissal from a religious institute - Stokłosa, Marek (Prawo Kanoniczne, 2024)
“Community life is an essential element of religious life, and ‘Religious are to live in their own religious house, observing community life, and are not to leave it without the permission of their superior’,” begins Pope Francis in his Apostolic Letter Communis Vita. In this motu proprio he introduces a new procedure to be applied by the major superior when he has determined that a religious is unlawfully and persistently absent, and cannot be located because he is deliberately evading contact. The purpose of this procedure is to bring about the dismissal ipso facto of such a member from the institute. “However,” Pope Francis notes, “the experience of recent years has shown that situations do arise involving unlawful absence from the religious house,” in which religious evade the authority of their lawful superior and cannot be found, having severed all contact with the institute. This inability to locate them makes it difficult for superiors to fulfil the canonical obligation to search for them and to initiate dialogue so that they may return to the religious community and persevere in their vocation (cf. can. 665 §2 CIC/83). Furthermore, such elusiveness impedes the initiation or completion of the dismissal procedure for a religious unlawfully living outside the community, as provided in can. 697–700 CIC/83, particularly because of the difficulty in delivering the canonical warnings when the religious’ whereabouts are unknown. For these reasons, it became necessary to amend can. 694 §1 CIC/83, which provides for the dismissal of a religious who has notoriously abandoned the Catholic faith or who has contracted or attempted to contract marriage, even merely civilly. The amendment adds a third cause of dismissal ipso iure: prolonged unlawful absence from the religious house lasting twelve uninterrupted months, taking into account the inability to locate the religious. To initiate this procedure, the major superior must first document the unlawful absence as well as the impossibility of finding the religious. He must then issue an appropriate declaration of these facts, specifying the date from which the twelve-month period begins, after which the religious will be dismissed from the institute ipso facto. When the twelve months have elapsed, the major superior, together with his council and after gathering the necessary evidence, is to issue without delay a declaration that the unlawful absence has lasted twelve months, so that the dismissal may be legally established (cf. can. 694 §2 CIC/83).